Hold my girl : a novel - Carr, Charlene (Sourcebooks Landmark, 2023)
"Two women. Two eggs. One life-changing switch. Katherine finally has it all. She's spent her entire life striving for perfection-obsessing over her spotless home, maintaining her pristine reputation, building her perfect family-and her hard work has finally paid off. After seven difficult years of trying (and failing) to conceive, Katherine gives birth to Rose, her IVF miracle child, and at last has the one thing she's wanted most of all. But one thing isn't quite perfect. Rose's pale skin doesn't match Katherine's complexion, and an irritating doubt begins to grow in Katherine's mind. Tess never got the happy ending she wanted. She underwent IVF at the same clinic as Katherine, but after finally conceiving, Tess's daughter was stillborn. Now, nearly one year later, she's approaching rock bottom. Consumed by her grief and without hope for the future, Tess is divorced, broke, and stuck in a dead-end job beneath her skillset. But shortly before Rose's first birthday, Katherine and Tess get a call from the fertility clinic: Their eggs were switched. As Katherine's carefully planned life begins to crumble around her, Tess finally sees the glimmer of hope she needed to get her life back on track. Motherhood has always been their dream, and neither woman is prepared to share that claim over Rose. It will take a tense custody battle to decide who deserves to be Rose's mother, but it will also push them to the brink. With themes of racial identity, loss, and betrayal, Hold My Girl is an emotional novel that will leave you contemplating: What makes a mother?"--